Vismia conduplicata (Hypericaceae), a new species from Mato Grosso, Brazil - Martins, Milena Ventrichi; Shimizu, Gustavo Hiroaki; Bittrich, Volker; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2018)
Vismia conduplicata, a new species of Hypericaceae from Mato Grosso state, Brazil, is described and illustrated. It is associated to “campos de murundus”, a kind of Cerrado physiognomy with woody plants growing on earth mounds, in a grassland matrix. The species was included in Vismia sect. Trianthera, based on the number of stamens per stamen fascicle and the number of ovules per locule. A comparison with the morphologically similar species Vismia micrantha is also provided.